THE EFFECT OF LEADERSHIP ON PERFORMANCE: Analysis of School Management Ability and Attitude - Ridwan, Ridwan (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2021)
School is a place to give birth to intelligent and virtuous human beings, and one of the most important elements are teachers and school principals. The good teaching carried out by teachers cannot be separated from the management system that applies in schools, and this is the authority of the principal. Therefore, this study wants to see the relationship and influence of leadership as an organizational attribute and as an individual on teacher performance. To prove the results of research scientifically, quantitative research methods, regression analysis techniques, and research instruments are used as the basis for data collection. The results of the study suggest that teacher performance does not stand alone, but is influenced by many factors, one of which is the school management system created by the leader. However, teacher performance will be better if the principal can actually carry out the management function wisely, both in terms of planning, regulation, supervision, and control (evaluation and assessment).